Karakteristik Pasien yang Mengalami Gangguan Jiwa di Wilayah Kerja Puskesmas Tamansari - Nia Restiana; Fani Sulistian (STIKes Karsa Husada Garut, 2017)
Mental disorders are maladaptive responses to stressors coming from both internal and external, resulting in a change in the functioning of the soul that causes disruption to the functioning of the soul, causing suffering to the individual and / or obstacles in performing the social role. The purpose of this study is to describe the characteristics of patients who have mental disorders in the work area of ​​Tamansari Puskesmas. The research design that will be used is descriptive method. The size of the sample is 24 patients. Demographic data of patients with mental disorders are mostly; (54%), primary education (10%), unemployment (21 persons (87%), unmarried status (14%) (58%). The greatest predisposing factor was the psychological factor of the closed personality (83%), the greatest precipitation factor was the loss of the loved one, the largest coping source was the personal ability (63%), whereas most nursing problems were hallucinations and isolation of 54% . This study is expected to provide information on the characteristics of psychiatric patients, the basis of consideration and thought in developing care for patients with mental disorders and can improve and develop effective intervention strategies in nursing care in patients with mental disorders.